The Usage of Hate Speech in Lithuanian Online Newspapers Publications about Refugees - Balsiūnaitė, Ieva (Žurnalistikos tyrimai, 2017)
The aim of this article is to analyse the concept of hate speech and how it is used in describing refugees in Lithuanian internet newspapers. The research shows the ways of how hate speech becomes a tool for constructing the portrait of refugees and describing other processes related to them, such as migration or integration. Presumptions of hate speech are also described in this article. Period of research: August – October, 2015. Lithuanian Internet newspapers that were analysed: “Delfi.lt”, “15min.lt”, “Lrytas.lt” and “Alfa.lt”. Work tasks: to analyse the concept of hate speech, to reveal the cases of hate speech in publications about refugees; to determine premises of the effect of hate speech expression in Lithuanian internet newspapers; to determine the connection between hate speech and journalistic work ethics; to give recommendations for recognizing and avoiding hate speech in the media. Having analysed academic literature and researched publications, it was concluded that hate speech connected to refugees is spread by using stereotypes, prejudices and racist statements. Refugees are often described as threatening strangers, who will not be able to integrate in European countries. Furthermore, according to elements of the hate speech used in articles analysed, refugees will harm European culture and make an impact on the security in different countries of Europe.
Keywords: hate speech; refugee; media; stereotype; prejudice; racism; discrimination; xenophobia; integration; discourse; analysis